"Poly (sulfur/oil) impregnated cotton: A newly developed material for effective oil removal from contaminated water". Issue 10 (21st September 2020) - Bajpai, Sunil Kumar; Dubey, Deepika
Abstract: In this work, a unique material has been developed by carrying out in situ co‐polymerization of sulfur and triglycerides (edible oil) within the cotton fibers to yield poly (sulfur/oil) impregnated cotton (PSOIC) composite material. The adsorbent was characterized by Fourier transform infrared, X‐ray diffraction, and SEM analysis. The equilibrium oil uptake studies were carried out in batch mode experiments and the sorption data were analyzed by various sorption isotherm models. The Langmuir model was found to be best fitted with maximum oil sorption capacity Qo of 9.52 g/g polymer. On the contrary, the conventional poly (sulfur/oil) adsorbent showed a Qo value of 2.35 g/g polymer, thus indicating the suitability and superiority of PSOIC over PSO material. The newly developed PSOIC material could be pressed in the form of sheets and was successful in removing oil/grease layer from the oil/water mixture. The adsorbent showed fair re‐generation capacity, thus minimizing the cost effectiveness to employ in large‐scale removal processes. Abstract :